A content analysis of women's experiences of different models of maternity care: the Birth Experience Study (BESt) - Helen Pelak; Hannah G. Dahlen; Hazel Keedle (BMC, 2023)
Abstract Background Pregnancy, birth, and early parenthood are significant life experiences impacting women and their families. Growing evidence suggests models of maternity care impact clinical outcomes and birth experiences. The aim of this study was to explore the strengths and limitations of different maternity models of care accessed by women in Australia who had given birth in the past 5 years. Methods The data analysed and presented in this paper is from the Australian Birth Experience Study (BESt), an online national survey of 133 questions that received 8,804 completed responses. There were 2,909 open-ended comments in response to the question on health care provider/s. The data was analysed using content analysis and descriptive statistics. Results In models of fragmented care, including standard public hospital care (SC), high-risk care (HRC), and GP Shared care (GPS), women reported feelings of frustration in being unknown and unheard by their health care providers (HCP) that included themes of exhaustion in having to repeat personal history and the difficulty in navigating conflicting medical advice. Women in continuity of care (CoC) models, including Midwifery Group Practice (MGP), Private Obstetric (POB), and Privately Practising Midwifery (PPM), reported positive experiences of healing past birth trauma and care extending for multiple births. Compared across models of care in private and public settings, comments in HRC contained the lowest percentage of strengths (11.94%) and the highest percentage of limitations (88.06%) while comments in PPM revealed the highest percentage of strengths (95.93%) and the lowest percentage of limitations (4.07%). Conclusions Women across models of care in public and private settings desire relational maternity care founded on their unique needs, wishes, and values. The strengths of continuity of care, specifically private midwifery, should be recognised and the limitations for women in high risk maternity care investigated and prioritised by policy makers and managers in health services. Trial registration The study is part of a larger project that has been retrospectively registered with OSF Registries Registration DOI https://doi.org/10.17605/OSF.IO/4KQXP .